FORMULASI SEDIAAN MASKER PEEL OFF DARI EKSTRAK ETANOL DAUN NANGKA KUNING (Artocarpus heterophyllus lam) - Widya Fitri; Daely, Ruth Christiani N; Sinaga, Arman Bemby; Ermanda, Fhonna Dara (Universitas Sari Mutiara Indonesia, 2021)
Background: Jackfruit leaves contain saponins, flavonoids, and tannins that can stimulate the growth of new cells in wounds. The benefits of yellow jackfruit leaves for the skin can smooth the skin, the antioxidant and anti-inflammatory content in jackfruit leaves is very good for warding off free radicals and repairing damaged skin tissue, acne scars, black spots or wounds on the body can quickly disappear. Peel-off mask is a cosmetic preparation for facial care in the form of a gel that is practical and has advantages in its use, namely after drying it can be immediately peeled off for 15-30 minutes. Objective: General purpose: to make a peel-off mask formulation from ethanol extract from yellow jackfruit leaves. Specific purpose: to determine and test the quality of peel-off mask preparations from ethanol extract of yellow jackfruit leaves. Methods: This study used an experimental method. The sample used in this study was yellow jackfruit leaves. Making yellow jackfruit leaf extract by extraction by maceration method using 96% ethanol as solvent. The concentration of the preparation is 2%, 4%, and 6%. Hasil: Penelitian sedian masker peel off yang dihasilkan semuanya homogen, sediaan masker peel off stabil, uji stabilitas selama 4 minggu tidak mengalami perubahan warna, bau dan bentuk, memiliki pH antara F0 7, F1 F2, dan F3 6. perbedaan konsentrasi ekstrak tidak berpengaruh signifikan terhadap daya sebar dengan konsentrasi 2%, 4% dan 6%. Uji sediaan mengering menghasilkan 15-30 menit, daya sebar F0 6,2 cm, F1 6cm, F2 5,6cm dan F3 5,8 cm. Kesimpulan: dari penelitian formulasi sediaan masker peel off dari ekstrak etanol daun nangka kuning dapat diformulasikan sebagai bahan aktif pada sediaan masker peel off.